A New Common Bacterial Blight Resistance QTL in VAX 1 Common Bean and Interaction of the New QTL, SAP6, and SU91 with Bacterial Strains. Issue 4 (1st July 2014) - Viteri, Diego M.; Cregan, Perry B.; Trapp, Jennifer J.; Miklas, Phillip. N.; Singh, Shree P.
ABSTRACT: Common bacterial blight (CBB) is a severe disease in common bean ( Phaseolus vulgaris L.). New resistance quantitative trait loci (QTL) should facilitate development of cultivars with high levels of resistance. Our objectives were to (i) identify new resistance QTL in VAX 1 and verify its presence in VAX 3, (ii) determine the interaction between QTL with existing SAP6 and SU91 QTL, and (iii) examine the interaction between QTL with less aggressive ARX8AC and aggressive Xcp25 bacterial strains. Sixty‐one F6:7 recombinant inbred lines (RIL) from 'Othello'/VAX 1 and 100 RIL from Othello/VAX 3 were screened in the greenhouse. Disease severity of inoculated primary leaves, first and second trifoliolate leaves, and pods, was scored from 1 = no symptoms to 9 = completely diseased. Genotyping was performed using 5398 single nucleotide polymorphism (SNP) BeadChip and CBB resistance QTL‐linked sequence characterized amplified region (SCAR) markers, SAP6 and SU91. A novel resistance QTL with major effect was detected on Pv11 linkage group in Othello/VAX 1 and verified in Othello/VAX 3. This Pv11 QTL, defined by the closest marker SNP47467 (45, 059, 806 bp), explained 23% of the phenotypic variance for resistance in primary and 18% in trifoliolate leaves in Othello/VAX 1, and 13% and 22%, respectively, in Othello/VAX 3 to ARX8AC. The Pv11 QTL, named Xa11.4 OV1, OV3, had greater influence against Xcp25, with respective values for variance for resistance explained in primary and trifoliolate leaves of 45% and 51% in Othello/VAX 1 and 26% and 37% in Othello/VAX 3. Conversely, SAP6 was only effective against ARX8AC in both populations, and surprisingly, SU91 was only effective against Xcp25 in Othello/VAX 3. SAP6 was the only QTL to condition resistance in pods. QTL interactions and differential reactions to strains indicate that the new Xa11.4 OV1, OV3 QTL is critical in breeding for stable and higher levels of foliage resistance to CBB in common bean.